Eficiência da revegetação para manutenção de aves em áreas de restinga no nordeste brasileiro: testes com translocação e interação frugívoros-plantas - Vieira-filho, Arnaldo Honorato (2012)
In this study two hypothesis related to the non-colonization of a 20 years old post mining reforested restinga area by the native avifauna from natural restinga forests were tested: (1) the distance between natural restinga forests and the reforested area does not allow colonization by 13 -common birds species tested; (2) the reforested area does not present the necessary structural organization to support the interactions between frugivorous birds-plants. To test the distance hypothesis, experimental translocations with 60% of 13 birds species individuals were performed between June/2008 and April/2010, and monitored until September/2011. From all the 125 individuals translocated to the reforested area, 58 were recaptured in the natural area and only one was recaptured in the reforested area, indicating that many individuals returned to their original area and remained in it. This result shows that the distance of 500 m between both areas does not constitute a barrier for colonization of the reforested area by the studied species, due to their capability of transposing open areas between patches. Therefore, the non-colonization of the reforested area by these species must be related to other causes. To test the hypothesis related to vegetation structure and composition frugivory events were recorded through direct observations and monthly capture of birds during one sampling year. Thus, it was possible to examine the dietary composition of frugivorous birds species and to construct interaction networks between frugivorous birds and plant species, calculating the importance index from plant species to frugivorous birds and vice-versa. The results showed a bigger compartmentalization at the reforested interactions network when compared to the natural area's one and also a replacement of the main species, both birds and plants, included in the interactions networks. This can be explained by the difference in composition of bird and plant species in the studied areas and by the lower plant richness and density in the reforested one. We can conclude that the studied reforested area does not present plant structure and composition able to support the interactions network between frugivorous birds-plants yet. So, the introduction of seedlings of those key plant species found in the natural area interactions network in the reforested area is suggested in order to provide a greater fruit availability and the maintenance of the frugivorous avifauna in the recovery area.